Pedagogic and Professional Competencies of Social Science Subject Teachers in Relation to Motivation and Learning Achievement - Yulia Desmita; Suarman Suarman; Gimin Gimin (Universitas Riau, 2021)
The quality of education is very dependent on teachers who play a role and are the biggest contributors in the world of education. Several competencies that must be possessed by teachers are increasing motivation and learning achievement of students, including pedagogical competence and professional competence. This study aims to identify and analyze the direct and indirect relationship between pedagogic and professional competence of social studies subject teachers in relation to the motivation and learning achievement of students. The total population in this study were 107 teachers of social studies subjects. The sampling technique used Isaac Michael's table with an error rate of 5%, the number of samples in this study were 80 social studies subject teachers. The process of sampling data used random sampling techniques with questionnaires and documentation. The collected data were then analyzed using descriptive analysis and path analysis. The findings in this study are that there is a positive direct and indirect relationship to the pedagogical and professional competence of social studies subject teachers in relation to the motivation and learning achievement of students. The level of motivation and learning achievement of students is related to pedagogical competence and professional competence. So that it is hoped that the teacher will improve on their pedagogic and professional competence and finally they can increase the motivation and learning achievement of students.